THE IMPACT OF IFRS ADOPTION ON EARNINGS MANAGEMENT IN BANKING COMPANIES IN INDONESIA STOCK EXCHANGE - Santy, Prima; Tawakkal, Tawakkal; Pontoh, Grace T. (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2016)
The issue of the IFRSadoption as a standard that can lead to a reduction of earnings management. The research aimed to give empirical evidence concerning the impact of the IFRS adoption on earnings management, and the test of the difference level of earnings management between before and after the IFRS adoption. The research scope focused on the implementation of IFRS adoption particularly in PSAK No. 50 and PSAK No. 55 (revised 2006) concerningfinancial instruments. The research objects were the banking companies listed in Indonesia Stock Exchange for 4 years (2008-2011), i.e. as many as 23 banks. Samples were taken by using the purposive sampling technique. The main variables in this research are IFRS and earnings management,and includes several control variable, among others are, size, financial leverage, market to book value and institutional investors. The data were analyzed usingmultiple regression analysis and different t-test analysis. The research result indicates that the IFRS adoption has not effect the decreaseon the earnings management.Among the four control variables, the variable institutional investor is found not to have theeffect on earnings management, whereas the other three variables haveeffect.The result of the different t-test analysis also indicates that statistically there is not significant difference on the level of the earnings management between before and after IFRS adoption. Thus, based on this study concluded that the adoption of IFRS still allow for the occurrence of earnings management.